Case Report: Post-gastrectomy reactive hyperinsulinemic hypoglicaemia: glucose trends before and after canagliflozin treatment - Bellastella, G.; Caruso, P.; Carbone, C.; di Nuzzo, M.; Scappaticcio, L.; Paglionico, V. Amoresano; Maiorino, M. I.; Esposito, K. (Frontiers in Endocrinology, 2023)
The pathogenesis of post-gastrectomy reactive hyperinsulinaemic hypoglycaemia is not yet fully clarified. Recent studies suggest an up-regulation of the intestinal glucose transporter SGLT-1 aimed to prevent carbohydrate malabsorption. The overexpression of SGLT-1 could therefore represents one of the mechanisms underlying the wide glycemic excursions found in patients after gastrectomy, but studies investigating the use of SGLT-1/SGLT-2 inhibitors in patients with post-gastrectomy reactive hyperinsulinemic hypoglycaemia are very scant in the literature. We report the case of a 37-year-old non diabetic man who frequently presented symptoms of hypoglycaemia in the postprandial period. In 2012, he underwent Roux en-Y gastric bypass (RYGB) and after two years, he started to experience typical symptoms of reactive hyperinsulinaemic hypoglycaemia. We suggested healthy modifications of dietary habits and periodic follow-up visits with a dietitian. After three months, the patient still presented symptoms of reactive hypoglycaemia; we provided him with Flash Glucose Monitoring (FGM) to assess trend of glucose levels in interstitial fluid during the day and we decided to introduce canagliflozin 300 mg/day before the main meal. Hypoglycaemic events previously referred by the patient and clearly recorded by FGM completely disappeared taking canagliflozin. We found a reduction of time spent in hypoglycaemia, an improvement of glycemic variability and an increase of time in target range. It was also noted a reduction of time spent in hyperglicemia with consequent improvement of average glucose values and of glucose main indicator. This is the first report with FGM supporting a role of canagliflozin in the management of post-gastrectomy reactive hyperinsulinaemic hypoglycaemia. Our preliminary results are very limited but in line with those of the literature and showed for the first time a reduction of hypoglycaemic events and an improvement of glycemic variability through a flash glucose monitoring system. Further studies are mandatory to confirm this therapeutic opportunity.